Cover Your Cough! A Short and Simple Activity to Demonstrate the Antimicrobial Effect of Desiccation - Jennifer Cook Easterwood (American Society for Microbiology, 2013)
Many undergraduate microbiology laboratory manuals include exercises demonstrating the antimicrobial effects of physical agents, such as UV light and heat, and chemical agents, such as disinfectants and antibiotics (3, 4). There is, however, a lack of exercises examining the effects of desiccation on bacterial growth and survival. This particular form of antimicrobial control is especially relevant today with an increased emphasis on coughing and sneezing into one’s sleeve or a tissue, where microbes will not contaminate hands and will eventually desiccate and die (2). Desiccation can have bacteriostatic or bactericidal effects depending on the species, the material on which the organism has desiccated, and the length of time. The absence of water can damage many cellular components, including enzymes, nucleic acids, and cell membranes (1). However, many prokaryotes have some degree of resistance to desiccation, with Escherichia coli surviving around 24 hours and Bacillus species surviving upwards of 300 years, though these numbers can vary due to a number of confounding factors (5). Some of these factors include the method by which desiccation occurred, whether desiccation occurred in a natural or laboratory situation, and the species itself (5). To address the effects of desiccation on bacterial growth and survival, a short, simple exercise was developed. By inoculating various materials with bacterial cultures and allowing them to air-dry for 24 hours, students can visualize the effects of desiccation by analyzing the growth, or lack thereof, when organisms are transferred to nutrient agar plates. This exercise has been used in a health professions microbiology course as well as a microbiology course for biology and biochemistry majors. It is short enough to be conducted during a standard lecture period or during a longer laboratory period in conjunction with other experiments demonstrating the effectiveness of physical agents on microbial growth